Compressed sensing cine imaging with high spatial or high temporal resolution for analysis of left ventricular function. Issue 2 (20th January 2016) - Goebel, Juliane; Nensa, Felix; Schemuth, Haemi P.; Maderwald, Stefan; Gratz, Marcel; Quick, Harald H.; Schlosser, Thomas; Nassenstein, Kai
Abstract : Purpose: To assess two compressed sensing cine magnetic resonance imaging (MRI) sequences with high spatial or high temporal resolution in comparison to a reference steady‐state free precession cine (SSFP) sequence for reliable quantification of left ventricular (LV) volumes. Materials and Methods: LV short axis stacks of two compressed sensing breath‐hold cine sequences with high spatial resolution (SPARSE‐SENSE HS: temporal resolution: 40 msec, in‐plane resolution: 1.0 × 1.0 mm 2 ) and high temporal resolution (SPARSE‐SENSE HT: temporal resolution: 11 msec, in‐plane resolution: 1.7 × 1.7 mm 2 ) and of a reference cine SSFP sequence (standard SSFP: temporal resolution: 40 msec, in‐plane resolution: 1.7 × 1.7 mm 2 ) were acquired in 16 healthy volunteers on a 1.5T MR system. LV parameters were analyzed semiautomatically twice by one reader and once by a second reader. The volumetric agreement between sequences was analyzed using paired t ‐test, Bland–Altman plots, and Passing–Bablock regression. Results: Small differences were observed between standard SSFP and SPARSE‐SENSE HS for stroke volume (SV; −7 ± 11 ml; P  = 0.024), ejection fraction (EF; −2 ± 3%; P  = 0.019), and myocardial mass (9 ± 9 g; P  = 0.001), but not for end‐diastolic volume (EDV; P  = 0.079) and end‐systolic volume (ESV; P  = 0.266). No significant differences were observed between standard SSFP and SPARSE‐SENSE HT regarding EDV ( P  = 0.956), SV ( P  = 0.088), and EF ( P  = 0.103), but for ESV (3 ± 5 ml; P  = 0.039) and myocardial mass (8 ± 10 ml; P  = 0.007). Bland–Altman analysis showed good agreement between the sequences (maximum bias ≤ −8%). Conclusion: Two compressed sensing cine sequences, one with high spatial resolution and one with high temporal resolution, showed good agreement with standard SSFP for LV volume assessment. J. Magn. Reson. Imaging 2016;44:366–374.